2001
DOI: 10.1074/jbc.m104730200
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Pyrin and the Apoptotic Speck Protein (ASC) Modulates ASC-induced Apoptosis

Abstract: Patients with familial Mediterranean fever suffer sporadic inflammatory attacks characterized by fever and intense pain (in joints, abdomen, or chest). Pyrin, the product of the MEFV locus, is a cytosolic protein whose function is unknown. Using pyrin as a "bait" to probe a yeast two-hybrid library made from neutrophil cDNA, we isolated apoptotic speck protein containing a caspase recruitment domain (CARD) (ASC), a proapoptotic protein that induces the formation of large cytosolic "specks" in transfected cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
258
1
2

Year Published

2002
2002
2007
2007

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 261 publications
(279 citation statements)
references
References 33 publications
13
258
1
2
Order By: Relevance
“…TMS1 may be another example of an NF-kB/JNK-regulated factor that functions in a proapoptotic capacity. Previous work from our lab and others has shown that TMS1 induces apoptosis when overexpressed (Masumoto et al, 1999;McConnell and Vertino, 2000;Richards et al, 2001;Ohtsuka et al, 2004). This apoptosis can be blocked by dominant negative mutants of caspase-9 and is dependent on Bax, implicating the mitochondrial pathway Ohtsuka et al, 2004).…”
Section: Discussionmentioning
confidence: 78%
“…TMS1 may be another example of an NF-kB/JNK-regulated factor that functions in a proapoptotic capacity. Previous work from our lab and others has shown that TMS1 induces apoptosis when overexpressed (Masumoto et al, 1999;McConnell and Vertino, 2000;Richards et al, 2001;Ohtsuka et al, 2004). This apoptosis can be blocked by dominant negative mutants of caspase-9 and is dependent on Bax, implicating the mitochondrial pathway Ohtsuka et al, 2004).…”
Section: Discussionmentioning
confidence: 78%
“…Pyrin has been shown to interact with ASC, 18 but whether this interaction leads to potentiation or inhibition of caspase-1 activation is still unclear. Based on evidence that a C-terminal truncation of pyrin in mice increased IL-1b processing while ectopic expression of WT pyrin in mouse RAW cells impaired IL-1b processing, a recent study proposed that the physiological function of pyrin is to inhibit the proteolytic activation of caspase-1 by sequestering ASC and preventing its interactions with caspase-1.…”
Section: Pyrin Induces Asc-dependent Caspase-1 Activationmentioning
confidence: 99%
“…The inflammasome component Asc has been described as an activator of procaspase-1 21 or as a modulator, leading to activation of procaspase-1 at low and inhibition at higher concentrations. 30 As the EBBP homolog Pyrin binds to Asc, 20 we tested if this is also the case for EBBP. Therefore, we performed co-IPs of HA-tagged EBBP and Asc fusion proteins tagged with an epitope of the vesicular stomatitis virus (VSV) or with a Flag tag.…”
Section: Ebbp Does Not Interact With Asc But With Procaspase-1 and Nalp1mentioning
confidence: 99%
“…This could prevent binding of procaspase-1 to Asc and its activation. 19,20 However, the strength and significance of a binding of Pyrin to Asc is controversial. 21 It is not known how the disease-causing mutations, which locate mainly to the carboxy-terminal RFP (SPRY; B30.2) domain, influence the amino-terminal pyrin domain.…”
Section: Introductionmentioning
confidence: 99%